(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The present study was designed to determine the protection afforded by different vaccination programs against the Newcastle disease virus. A serological survey on the prevalence of antibodies to Newcastle disease virus (NDV) was carried out in broilers chicken in Dinajpur districts. For this reason, a total of 75 serum samples were collected form broiler chickens and samples were divided into five groups, each group contain 15 chickens. Group E did not receive any vaccine and served as a negative control group. Groups A-D were vaccinated with different vaccination programs against NDV. From this experimental work the principal objectives of the present investigation it may be stated that production of Hl-antibody was higher in birds of group D vaccinated with CevacVitapest-LR compared to those of group A vaccinated with Medivac NDLaSotaR, group B vaccinated with BCRDV(R) and group C vaccinated with Izovac. B, HitchnerR. Thus, the CevacVitapest-LR was found to be superior to some extent than Medivac ND-LaSota, BCRDVR, Izovac B, Hitchnert. However, as regards vaccination of chicks against NDV in earlier days the use of lentogenic strains are recommended although it should be kept in mind that vaccination with LaSota strains would cause considerately greater problems in young susceptable birds than Hitchner B1 strain and even through LaSota induces a stronger immune response. Asian Australas. J. Biosci. Biotechnol. 2018, 3 (1), 52-58